Case Report: Hemoperfusion Efficiency in Paraquat Toxicity - Ostadi, Ali; Paeezi, Maryam (International Journal of Medical Toxicology and Forensic Medicine, 2019)
The present study was conducted on paraquat poisoning cases, from January 2017 to January 2018, a total of 9 patients of paraquat poisoning transferred to our referral Toxicology center. Six of them survived. Paraquat is one of the most used herbicides, a non-selective, killing green plants on contact. It is very toxic for human. We used immunosuppressant and antioxidant drugs in most cases. In addition, many patients were given gastrointestinal decontamination and activated charcoal at a local hospital before transferring to our center. According to our treatments, early management and hemoperfusion after ingestion can increase the rate of survival.